(untitled) (Semiárida, 2022)
In the forests of tropical and subtropical America, extensive livestock farming is typically the common production system and is generally carried out on native forest surfaces and in deforested areas. Bolivia has an area of 1,098,581 km2 and is one of the countries that has the greatest wealth in natural resources, with variability in climate, topography, natural vegetation and soils. Important areas of this country are destined for livestock production and particularly in the Serranía del Iñao National Park and Integrated Management Natural Area (PN-ANMI Serranía del Iñao). Historically, continuous grazing has been carried out in these areas without any regulation of the animal load that takes into account both the capacity of the farm and the availability and production of forage. This livestock breeding system, characterized by the "non-management" of the herd or forage resources, causes the loss of the richness of forage species, increase and invasion of undesirable species, soil degradation, reduction of livestock production and impact on fauna. As a consequence, the following questions arose: How does the stocking rate of cattle influence the vegetation and soil in the montane forest of Iripiti, PN-ANMI Serranía del Iñao? What are the native forage species and of these the most important ones? a silvopastoral system? How do species respond to grazing? The hypothesis raised was whether different grazing intensities cause changes in the structure, composition and floristic diversity, apparent density and organic matter of the soil. Consequently, the general objective was to identify the effect of grazing pressure on vegetation and soil in the communities of Yuqui and Iripiti, located in the Serranía del Iñao National Park and Integrated Management Natural Area (PN-ANMI Serranía del Iñao ). Three sampling sites were selected. The topographically isolated Anta canyon at the entrance of the cattle was the site without grazing (Site 1) and two with different grazing pressure: Doña Hilda’s ranch as moderate grazing (Site 2) and the third, Don Gómez ranch as intense grazing (Site 3), with 0.22 and 0.43 animals.ha-1 respectively. In each of them, ten transects of 1000 m2 (0.1 ha) were installed, where vegetation and soil evaluations were carried out. From a general point of view, the textural differences found between the soils of the three sampling sites can be attributed to different pedogenetic processes associated with topographic factors. It is evident that grazing does not have a direct effect on these processes but in some cases it can contribute to the increase in the deposition of fine materials, such as silt and clay, by reducing the vegetation cover on the soil and through trampling that facilitates subsequent transportation from slopes and higher areas towards the lower flat areas, a very notable phenomenon in the rainy season. In each of the three sites, plant species were observed with high values of frequency and abundance that characterize them and that are common in the montane forest. From the point of view of forage production, important differences are observed between the three sites in terms of the number of species, their abundance-cover and their forage level. The presence of a high proportion of forage-grade species Excellent Forage (EF) and Forage (F) exclusive to Site 1 stands out, while in the sites with grazing the species of the Poor Forage (PF) and Non-Forage (NF) groups ) are more representative in terms of coverage abundance. From the point of view of the dynamics of the species facing grazing in Site 1, decreasing species predominated while the species considered Invasive were absent and with higher abundance-cover values in the grazed sites. These species dynamics from a closed situation and two grazing situations clearly show that the action of domestic herbivores notably affects the composition of the plant community of the montane forest. The notable change observed between the closure situation and the grazing situations is key to asserting that the majority of pristine species in these areas lack adaptations or strategies to tolerate grazing by domestic livestock and furthermore, that the type of grazing that is carried out in these areas is not at all adequate for the conservation of the species of these forests. It is well known that continuous grazing is one of the main disturbances with markedly negative consequences on the composition and production of these areas and taking into account these results, it is of utmost importance to think and design management strategies according to the floristic composition and structure. of these forests with the aim of recovering and conserving species of good value f Director: Estelrich, Héctor Daniel